2019
DOI: 10.3390/vaccines7030115
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Analysis of a CCHFV mRNA Vaccine Candidate in Mouse Models

Abstract: Development of new vaccine platforms against viral diseases is considered urgent. In recent years, mRNA constructs have attracted great interest in this field due to unique advantages over conventional gene transfer platforms. In the present study, we developed a new naked conventional mRNA vaccine expressing the non-optimized small (S) segment of the Ank-2 strain of Crimean-Congo Hemorrhagic Fever virus (CCHFV). We then analyzed its single and booster dose immunogenicity and protection potential in the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…In an immunocompetent mice, NP based CCHFV vaccines developed with different platforms, uniformly induced IL-2, IL-10, IL-6, Il-4, TNF-α and IFN-γ [ 59 ]. In a CCHFV NP based mRNA vaccine study, IFN-γ an IL-4 levels were high in vaccinated mice before challenge [ 60 ]. The results from our study shows that rNP induced cytokines that could indicate balanced Th1/Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…In an immunocompetent mice, NP based CCHFV vaccines developed with different platforms, uniformly induced IL-2, IL-10, IL-6, Il-4, TNF-α and IFN-γ [ 59 ]. In a CCHFV NP based mRNA vaccine study, IFN-γ an IL-4 levels were high in vaccinated mice before challenge [ 60 ]. The results from our study shows that rNP induced cytokines that could indicate balanced Th1/Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…Even though nucleoside-modified mRNA-LNP-based vaccine candidates have been used in vaccine studies against several infectious diseases ( 7 16 ), it has not been evaluated against CCHFV infection. However, naked mRNA, based on the S-segment of CCHFV (Ank-2 strain), has previously been used to immunize IFNAR −/− mice prior to CCHFV challenge ( 26 ), with a difference in success based on the immunization schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the immune response to this formalin inactivated vaccine have demonstrated that after four doses, low levels of neutralising antibodies are induced (112). Multiple other vaccine candidates for CCHFV have been developed using a wide range of platforms to deliver vaccine antigens (113)(114)(115)(116). For example, two doses of a protein-based subunit CCHFV vaccine that targeted Gn and Gc of the glycoprotein precursor achieved neutralising antibody responses, but did not confer protection in mouse challenge models (117).…”
Section: Controlling Zoonotic Transmission Of Cchfvmentioning
confidence: 99%